Solaris™ 8 System Administrator's Reference - Winsor, Janice (Pearson, 2000)
Get beyond the man pages! The practical, task-oriented reference to every key Solaris 8 command, from ab2admin to zic System/network administration, file systems, printing, Internet services, editing, shell programming, and more Convenient, comprehensive, and accessible! The essential resource for every Solaris 8 sysadmin, Web professional, developer, and power user! If you're a Solaris user, sysadmin, or developer, you know how tough it is to rely on the man pages when you need fast answers. Now, there's a superb alternative: Solaris 8 System Administrator's Reference . In this book, Solaris expert Janice Winsor presents more than 1,300 pages of solid reference information, organized for maximum accessibility and quick problem solving. Winsor begins with a convenient cross-reference and list of tasks, identifying all the commands you're likely to need in each problem category-so you don't need to know a command's name before you can get information about it. Next, she provides comprehensive descriptions, usage examples, and reference tables for nearly 400 Solaris 8 and Solaris 7 commands, including: Printing File system management System status and administration Editing Networking and Internet services Shell programming, and much more Say goodbye to the man pages, and say hello to the most authoritative, intelligible, user-friendly, and just plain valuable Solaris reference ever created: Solaris 8 System Administrator's Reference by Janice Winsor.